Workshop Peningkatan Aktivitas Jasmani dan Mengurangi Perilaku Sedenter pada Siswa SD Muhammadiyah di Yogyakarta: Physical Activity and Sedentary Behavior Workshop for Muhammadiyah Elementary School Students in Yogyakarta - Priambadha, Aprida Agung; Andriyani, Fitria Dwi; Setyawan, Feri Budi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
This community service effort aimed to organize a workshop for administrators, Physical Education instructors, and class teachers at Muhammadiyah elementary schools in Yogyakarta. The goal was to raise participants' awareness and insight about the pressing issue of children's lack of physical exercise and their excessive use of screen-based devices, which must be addressed. The community service took the form of a workshop, and it was organized in partnership with the Muhammadiyah Central Leadership's Sports Development Institute (LPO), the Muhammadiyah Elementary and Secondary Education Council, and the Muhammadiyah Yogyakarta Regional Management. The activity was funded by the 2024 Batch VII Research Grant and the LPO PP Muhammadiyah. The workshop was held on July 10, 2024, at the Amphitheater A Building, Faculty of Medicine, Universitas Ahmad Dahlan. The registered participants included 22 principals, 22 elementary school classroom teachers, and 33 physical education, sports, and health teachers. The study revealed a substantial increase in participants' understanding of the current WHO 2020 guidelines for physical activity and sedentary behavior (p < 0.05). This initiative resulted in workshop modules, articles in online and social media, as well as community service journals.